2017
DOI: 10.29050/harranziraat.303016
|View full text |Cite
|
Sign up to set email alerts
|

Şanlıurfa Yöresi Zeytinliklerinin Beslenme Durumunun Belirlenmesi

Abstract: ÖzBu araştırma, Şanlıurfa merkez ve ilçelerinde bulunan bazı zeytin bahçelerinin genel beslenme durumlarını tespit etmek amacıyla 2010-2011 yılları arasında yürütülmüştür. Bu amaçla; yöreyi temsilen Şanlıurfa merkez ve ilçelerde bulunan zeytin bahçelerinin 17 tanesinden yaprak örnekleri ile 0-20 ve 20-40 cm derinliklerden toprak örnekleri alınıp, analiz edilmişlerdir. Elde edilen bulgulara göre toprakların genel olarak çok kireçli, hafif alkalin yapıda, tuzsuz ve organik madde miktarının yetersiz olduğu tespit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to the limit values reported by Richards 1954, the total salt content of the soil samples was determined as salt-free (Table 2). In the same region, the general nutrition status of some olive orchards located in the center and districts of Şanlıurfa was investigated by Söylemez et al (2017) who also reported that all of the % salt contents of soils were in the salt-free class.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the limit values reported by Richards 1954, the total salt content of the soil samples was determined as salt-free (Table 2). In the same region, the general nutrition status of some olive orchards located in the center and districts of Şanlıurfa was investigated by Söylemez et al (2017) who also reported that all of the % salt contents of soils were in the salt-free class.…”
Section: Resultsmentioning
confidence: 99%
“…Wolf (1971) in terms of boron boundary values in the soil compared to the province of Şanlıurfa Siverek district in terms of boron content of wide soil groups at a depth of 0-20 cm 65.78% very little (<0.4 mg / kg), 26.32% less (0.5-0.9 mg / kg, 7.90% was sufficient (1.0-2.4), at 20-40 cm depth, 81.58% was found to be very small, 15.79% was low and 2.63% was sufficient (Table 2). The aim of the study was to determine the general nutritional status of some olive orchards in the center and districts of Şanlıurfa in the same region Söylemez et al (2017) reported similar results.…”
Section: Texture Ph Salt Lime Organic Mattermentioning
confidence: 94%
See 2 more Smart Citations